2021
DOI: 10.15789/2220-7619-hit-1798
|View full text |Cite
|
Sign up to set email alerts
|

Herd immunity to SARS-CoV-2 among the population of the Republic of Belarus amid the COVID-19 pandemic

Abstract: Objective was to investigate the SARS-CoV-2 collective immunity status of the population of Belarus within the context of the COVID-19 pandemic. Materials and methods. The work was carried out according to the methodology for assessing SARS-CoV-2 population immunity, developed by Rospotrebnadzor Russia and the Ministry of Health of Belarus with the participation of the St. Petersburg Pasteur Institute, taking into account WHO recommendations. The Bioethics Committee of Belarus and the local ethics committee of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
2
16
0
2
Order By: Relevance
“…This article continues our previous publications analyzing SARS-CoV-2 Ab seroprevalence, such as our cross-sectional study of herd immunity in the St. Petersburg population [14] conducted in the early period of COVID-19 incidence (13-20/06/2020), as well as longitudinal seromonitoring of the population in 26 regions of Russia [15][16][17][18][19][20]. Features of seroprevalence in Belarus and Kyrgyzstan (2020-21) were also analyzed [21,22]. The aim of the study was to monitor the seroprevalence of Abs to Nc and RBD in the St. Petersburg population during the COVID-19 pandemic in 2020-21.…”
Section: Introductionsupporting
confidence: 59%
“…This article continues our previous publications analyzing SARS-CoV-2 Ab seroprevalence, such as our cross-sectional study of herd immunity in the St. Petersburg population [14] conducted in the early period of COVID-19 incidence (13-20/06/2020), as well as longitudinal seromonitoring of the population in 26 regions of Russia [15][16][17][18][19][20]. Features of seroprevalence in Belarus and Kyrgyzstan (2020-21) were also analyzed [21,22]. The aim of the study was to monitor the seroprevalence of Abs to Nc and RBD in the St. Petersburg population during the COVID-19 pandemic in 2020-21.…”
Section: Introductionsupporting
confidence: 59%
“…Unfortunately, there are currently no published studies that have been conducted according to a single methodology with different countries globally when examining epidemic process dynamics as was done here. In on our experience, assessment of SARS-CoV-2 collective immunity, carried out according to a single methodology [69] at different stages of the epidemic in Russia [8, 70], Belarus [71], and Kyrgyzstan [72], showed that there is successful formation of herd immunity in those countries. Those countries were discussed in our earlier work, and usage of vector and whole-virion vaccines usage dominates in them.…”
Section: Discussionmentioning
confidence: 99%
“…В Республике Беларусь в эпидемическом процессе COVID-19 установлены последовательные этапы развития -от отсутствия случаев в начале 2020 года до выявления случаев инфекции, при которых большинство заболевших не отмечали в анамнезе контакт с пациентами с COVID-19, сопровождающиеся периодами подъема и спада заболеваемости [1,2].…”
Section: Discussionunclassified